Diagnostik Kesulitan Belajar Siswa Kelas V Pada Materi KPK Dan FPB Di SDN 2 Balangnipa - Nurhalisa Nurhalisa; Nurjannah Nurjannah (Pedagogy: Journal of Multidisciplinary Education, 2025)
The aim of the research is to determine the causes of difficulties experienced by students in solving FPB and KPK questions. This research is a qualitative descriptive study. This research was conducted at SDN 2 Balangnipa on May 11 2024. The subjects of this research were class V students at SDN 2 Balangnipa with the initials NL and AN who are female. Topic selection is based on fifth grade students' mathematical abilities and vision. Data collection methods in this research are diagnostic tests, observation and interviews. Regarding the results obtained, it was concluded that the average learning difficulties experienced by the subjects were a lack of understanding of concepts, also poor memory about multiplication and a lack of understanding about exponential numbers. Because of this, lessons have passed so that students' understanding becomes reduced or memory is lost over time. To be able to finish. Understanding the multiplication and division material is of course because there are difficulties experienced. This is in accordance with the learning difficulties faced by students. Teachers need to ensure that students understand concepts and can communicate effectively about the material they teach.